Assessing the sustainability of higher education’s institutions from the perspective of Algerian Universities’ teaching staff - Khaldi, Hassina; Mekimah, Sabri (Milev Journal of Research and Studies, 2022)
The aim of this study is to assess the sustainability of higher education’s institutions from the point of view of Algerian universities’ teaching staff, We relied on descriptive and analytical method, using electronic questionnaire as a data collection tool, it was distributed to a random sample of 381 teachers, 276 questionnaires were retrieved with a response ratio of (72%) descriptive statistical and deduction tools have also been used to analyse and test the hypotheses of the study using the spss program, The study found that higher education institutions do not apply sustainability from the point of view of the Algerian universities’ teaching staff. The study recommends that Algerian universities should be interested in developing a clear strategic vision for sustainability through the establishment of environmental and sustainability committees ,and take advantage of the universities' successful experiences in the field of university sustainability.